The Value of Patriotism in The Lone Survivor Film - Wulan, Tri; Purwanto, Andri (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
The aim of this research is to identify and analyze the value of patriotism displayed in the film Lone Survivor. The theory used in analyzing the value of patriotism is Rashid's theory and divides the value of patriotism into 7 values, namely loyalty, courage, self-sacrifice, love, never giving up, caring and optimism. The research method used is descriptive qualitative. As for research techniques using librarian techniques that focus on books and journals as supporting theory in this study. The results of the analysis show that there is a loyalty value of 1 data with a percentage of 3.3%, a value of courage totaling 5 data with a percentage of 16.7%, the value of willingness to sacrifice is 2 data with a percentage of 6.6%, the value of love is 3 data with a percentage of 10%, the value of caring is 6 data with a percentage of 20%, the value of never giving up is 7 data with a percentage of 23.4% and the optimistic value is 6 data with a percentage of 20%. Thus it can be concluded that the most dominant value is the value of never giving up.